2014
DOI: 10.1002/ajmg.a.36677
|View full text |Cite
|
Sign up to set email alerts
|

An osteosclerotic form of Robinow syndrome

Abstract: Robinow syndrome (RS) is a clinically and genetically heterogenous condition primarily characterized by short stature, mesomelia, genital hypoplasia, oral abnormalities, and a facial gestalt that includes hypertelorism, a short nose, and a broad mouth. The disorder exists in both a dominant and a more severe recessive form. Here two unrelated cases of sporadic RS are described with the additional finding of axial and appendicular osteosclerosis. These two patients, coupled with three additional patients previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Regarding anomalies in the head and neck region, Bunn et al described an osteosclerotic form of RS. They reported radiographic findings of a sclerotic head and thickened bone [8]. In the present patient, lateral cephalometry and CT of the skull showed osteosclerosis.…”
Section: Discussionsupporting
confidence: 55%
“…Regarding anomalies in the head and neck region, Bunn et al described an osteosclerotic form of RS. They reported radiographic findings of a sclerotic head and thickened bone [8]. In the present patient, lateral cephalometry and CT of the skull showed osteosclerosis.…”
Section: Discussionsupporting
confidence: 55%
“…2). However, osteosclerotic phenotypes in a subset of patients with Robinow syndrome (133) suggest reciprocal WNT/β-catenin signaling activation in the bone, and Robinow syndrome-like phenotypes in mice with null and hypomorphic Prickle1 alleles (134) suggest the involvement of core PCP components other than DVLs in Robinow syndrome. Signaling mechanisms and Robinow syndrome genes should be further investigated.…”
Section: Human Diseases Related To Core Pcp Componentsmentioning
confidence: 99%
“…As is the case with other conditions known to cause cranial osteosclerosis, this can result in certain comorbidities. In particular, bilateral mixed hearing loss had been reported in four subjects with the osteosclerotic form of RS before (Bunn et al, 2014; Eijkenboom et al, 2012; Kelly et al, 1975; White et al, 2015). One of these subjects had evidence of hyperostosis of the skull, appositional bone growth of the middle ear walls with narrowing of the internal auditory canals, and thickened malformed ossicles found on CT scan.…”
Section: Discussionmentioning
confidence: 95%
“…Based on DEXA scan imaging, we were able to identify a characteristic pattern of structural anomalies of the bones. While the osteosclerotic form of RS had been briefly reported before, it had not been explored in much depth until Bunn et al (Bunn et al, 2014) performed a DEXA scan on two subjects found to have significantly increased BMD. Our findings suggest that this is may be a much more common feature of RS with varying degrees of severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation